The Level of Self-Organized Learning among Middle East University Students in Jordan - Mahameed, Mohammed Ibrahim (Journal of Educational and Psychological Sciences, 2022)
Self-organized learning is an active structure process through which creative skills can be developed among the students of the various stages, it helps to train them to formulate ideas and express feelings well. So, this study aimed at investigating the level of self-regulated learning components among university students, and whether these components differ according to the student’s gender and academic level. The sample of the study consisted of (331) male and female undergraduate students from Middle East University. To achieve the aims of the study, Ahmad’s (2007) self-regulated learning scale was used. The results of the study revealed that the students’ level of self-regulated skills on the rehearsing and memorizing component was high, whereas the level of the rest of the components was moderate, where male students scored significantly higher than female students on the goal setting and planning component. The results also revealed that there were no statistically significant differences in self- regulated learning and academic level. The study recommended more studies that address the effect of using self-organized learning strategies on academic attitudes and academic achievement.